2011
DOI: 10.1007/s11104-011-0850-7
|View full text |Cite
|
Sign up to set email alerts
|

Microsite and litter cover effects on soil conditions and seedling recruitment in a saline agricultural system

Abstract: Successful revegetation of saline land is dependent on seedling recruitment to maintain vegetative cover for lowering of saline water tables and agricultural production. This paper examines seasonal effects of tree/shrub microsites and leaf-litter on soil conditions and seedling recruitment in a saline grazing system planted with Eucalyptus sargentii Maiden tree rows (15 years old) and saltbush (Atriplex spp.) interrows (8 years old). Salt bush rows were also slightly mounded. As litter accumulation decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The results from both shade houses and leafless forests demonstrated that the germination of seeds covered by litter and soil was the most hindered among all the positions as the shading degree became larger than 40%. The main reason for these differences was the variations in the microenvironment (e.g., light, temperature) dictated by the seed position (Pons, 1992;Farrell et al, 2011). As shown in Table 1, the temperature fluctuation among seed positions at each shading degree was subtle, while the light conditions were greatly changed with the modification of seed position.…”
Section: Similar Germination Percentages Under Leafless Canopy and Inmentioning
confidence: 99%
“…The results from both shade houses and leafless forests demonstrated that the germination of seeds covered by litter and soil was the most hindered among all the positions as the shading degree became larger than 40%. The main reason for these differences was the variations in the microenvironment (e.g., light, temperature) dictated by the seed position (Pons, 1992;Farrell et al, 2011). As shown in Table 1, the temperature fluctuation among seed positions at each shading degree was subtle, while the light conditions were greatly changed with the modification of seed position.…”
Section: Similar Germination Percentages Under Leafless Canopy and Inmentioning
confidence: 99%
“…In warm dry climates, restoration efforts may be hampered by the lack of soil cover, typically provided by standing vegetation and litter. At mid-day during summer months, dark, exposed soils may become extremely hot, providing an inhospitable environment for seed germination and seedling growth (Farrell et al 2011). In warm climates, soil cover will decrease soil moisture loss (Shay et al 2001;, reduce soil temperatures (Hogg and Lieffers 1991;, and protect seedlings from the desiccating effects of wind (Facelli and Pickett 1991).…”
mentioning
confidence: 99%
“…Other environmental factors at the recipient site also contributed to the seedling survival, and thus the interaction effect of soil source and recipient site had significant effects on both survival of seedlings and of species in the second year. Amount of PAR was probably one of the factors determining the survival percentage of seedlings under different canopies [34,35]. All plots at the young forest site were under tree canopies, where PAR was very low, whereas at the grass site it was too intense (Figure 2) for seedlings.…”
Section: Discussionmentioning
confidence: 99%